2009
DOI: 10.1111/j.1349-7006.2009.01136.x
|View full text |Cite
|
Sign up to set email alerts
|

Stimulatory heterotrimeric GTP‐binding protein augments cisplatin‐induced apoptosis by upregulating Bak expression in human lung cancer cells

Abstract: The present study aimed to investigate the effect of the stimulatory heterotrimeric GTP-binding (Gs) protein signaling system on cisplatininduced apoptosis of lung cancer cells and its underlying mechanism as an attempt to develop a novel strategy to improve the therapeutic efficacy of cisplatin. Overexpression of the constitutively active a subunit of Gs (GasQL)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 26 publications
0
8
0
Order By: Relevance
“…We previously reported that the cAMP signaling system regulated lung cancer cell apoptosis through various mechanisms (that is, by modulating the expression of Bcl-2 family proteins 35, 36 and by regulating ataxia-telangiectasia-mutated (ATM) activation in lung cancer cells 37 ). Here, we introduce the repression of TIPRL expression by a HDAC8 expression increase as a novel mechanism by which cAMP signaling modulates apoptosis.…”
Section: Discussionmentioning
confidence: 99%
“…We previously reported that the cAMP signaling system regulated lung cancer cell apoptosis through various mechanisms (that is, by modulating the expression of Bcl-2 family proteins 35, 36 and by regulating ataxia-telangiectasia-mutated (ATM) activation in lung cancer cells 37 ). Here, we introduce the repression of TIPRL expression by a HDAC8 expression increase as a novel mechanism by which cAMP signaling modulates apoptosis.…”
Section: Discussionmentioning
confidence: 99%
“…Choi, et al show that the expression of constitutively activated Gα s in the A549 and H1299 human lung cancer cell lines augments cisplatin induced apoptosis through the modulation of Bcl-2 family proteins, specifically the up regulation of BAX and BAK and the down regulation of Bcl-2 and Bcl-xL [120]. Conversely, Seo, et al .…”
Section: Note: Added In Proofmentioning
confidence: 99%
“…This in turn regulates the expression of other genes (6). cAMP signaling also modulates cancer cell death induced by anticancer drugs and ␥-rays (7,8).…”
mentioning
confidence: 99%